Murabahah Financing as an Engine oof Growth: Analysis of Contribution and Integrated Risk Management at BMT Alif Mandiri Makassar - Rostini (Economics and Business Journal (ECBIS), 2026)
The development of Islamic microfinance institutions requires the implementation of financing schemes that are not only compliant with Sharia principles but also capable of maintaining financing quality and sustainability. One of the most widely applied contracts is murabahah financing, particularly in supporting Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the implementation of murabahah financing and the risk mitigation strategies applied at BMT Alif Mandiri Makassar. This research employs a qualitative approach with a descriptive-analytical method. Data were collected through field observations, in-depth interviews with management and financing officers, and documentation studies. The findings indicate that murabahah financing at BMT Alif Mandiri Makassar is implemented regularly through several stages, including application submission, feasibility analysis, financing approval, contract realization, and post-disbursement monitoring. The financing analysis emphasizes repayment capacity, members' character, and the suitability of financed goods for productive business needs. Risk mitigation strategies are conducted through careful customer character assessment, direct business verification, proportional margin determination, the use of collateral as a financing safeguard, and continuous monitoring. This study concludes that productive murabahah financing supported by integrated risk management practices is an effective and sustainable financing instrument for the development of MSMEs within Islamic microfinance institutions